THE EFFECT OF CORPORATE GOVERNANCE TO REAL EARNINGS MANAGEMENT WITH AUDIT QUALITY AS A MODERATING VARIABLE EMPIRICAL STUDY ON COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - M. Anwar Masruri; Vinola Herawaty (Jurnal Magister Akuntansi Trisakti, 2017)
This research is conducted in the period 2013 to 2015 and the selected sample with purposive sampling method using criteria that have been determined. Samples are selected for companies that present the required data in this study. A total of 75 sample companies that have criteria based on this sample selection method. The method of analysis applied in this research is quantitative method and statistical analysis used is multiple regression analysis.The result of the research shows that CG variable has significant negative effect on REM_Index model, Audit Quality variable strengthen negative correlation between Corporate Governance and Real Earnings Management significantly, Audit Quality and Company Size negatively affect REM_Index model on Abn_CFO model, Audit Quality variable proved to influence Abn_CFO. Abn_DisEx variable model of Corporate Governance proved negatively significant to Abnormal Discreationary Expenses and Abn_Prod Models Moderation and Company Size Model has a significant positive effect on Abnormal Production Cost.